Electro-optical properties of high birefringence liquid crystal compounds with isothiocyanate and naphthyl group - 彭增辉 王启东 王少鑫 姚丽双 刘永刚 胡立发 曹召良 穆全全 杨程亮 宣丽 (Chinese physics B, 2017)
Liquid crystal（LC） compound with isothiocyanate and naphthyl group is an attractive high birefringence LC material,and can be used in optical devices. In this paper, the electro-optical properties of a series of this type of LC compounds were investigated. The melting points and enthalpy values of these LC compounds were higher than those of corresponding compounds with the phenyl group. These compounds exhibited high birefringence with a maximum value of 0.66. Fluorine substitution in the molecular almost does not affect the birefringence value. When these LC compounds with the naphthyl group were dissolved in a commercial LC mixture, the electro-optical properties depending on temperature were investigated. In the low-temperature region, LC mixtures with the naphthyl-group LC compounds exhibited higher viscosity than pure commercial LCs. In the high-temperature region, viscosity values very closely approached each other. When response performance was investigated, figure-of-merit（FoM） values were measured. The Fo M values of LC mixtures containing LC compounds with naphthyl group were lower than those of reference benzene LCs in the low-temperature region. However, in the high-temperature region, the results were reversed. These isothiocyanate LC compounds with naphthyl group can be applied in special fast-response LC device, particularly the ones used under high-temperature conditions.